Veline, ordinary women and male savages: Disentangling racism and heteronormativity in contemporary narratives on sexual freedom. Issue 2 (28th March 2018) - Gribaldo, Alessandra
Abstract : This article takes as its starting point the so-called 'sex scandals' surrounding Italy's former prime minister Silvio Berlusconi during the last years of his premiership (2009–2011), which have filled Italian newspaper columns and legal case files. Political discourses and media interpretations of women's freedom at the time represented genders through the eroticisation of power. The deployment of postfeminist and stereotyped representations of gender relations produced a complex and ambivalent frame for female sexuality and agency which reproduced the hegemonic neoliberal rhetoric that locates freedom and emancipation in the market. This narrative was further inflected by class and race, as it was deployed through the opposed images of white, Italian, respectable, caring women, and cynical young women and migrants using their bodies as a resource in a sexual-economic exchange with men occupying positions of power. Through feminist reflections on work I frame and discuss the use of the notions of choice and freedom in these discourses. Shifting the focus from women's behaviour to the analysis of a peculiar image of masculinity displayed by the then premier, the article highlights how racism, colonial legacies and homophobia are enmeshed in this historically and culturally based gender imagery. Italian summary: L'articolo è una riflessione a partire dai cosidetti 'scandali sessuali' che hanno riguardato il primo ministro Silvio Berlusconi durante gli ultimi anni del suo governo (2009–2011) e riempito le colonne dei giornali e i fascioli giudiziari. I discorsi politici e le interpretazioni mediali sulla libertà delle donne del periodo rappresentavano i generi attraverso l'erotizzazione del potere. Il dispiegarsi di rappresentazioni post-femministe e stereotipate delle relazioni di genere andavano a formare un quadro complesso e ambivalente sull' agency e la sessualità femminile riproducendo la retorica egemonica leoliberista che posiziona la libertà e l'emancipazione nel mercato. L'autodeterminazione delle donne nell'uso del proprio corpo dunque si sovrapponeva alla ratificazione degli squilibri di potere tra generi. Questa narrazione aveva degli accenti di classe e razza, in quanto si articolava attraverso le opposte immagini delle donne bianche italiane accudenti e rispettabili contro ciniche giovani donne e migranti che usavano il loro corpo come una risorsa nello scambio sessuo-economico con uomini che occupavano posizioni di potere. Attraverso la riflessione femminista sul lavoro rintraccio e tratto l'uso delle nozioni di scelta e libertà in questi discorsi. Spostando l'attenzione dal comportamento delle donne all'analisi della specifica immagine di mascolinità portata avanti dall'ex premier l'articolo sottolinea come razzismo, eredità coloniale, e omofobia siano implicate in un immaginario di genere culturalmente e storicamente connotato.